Realism in The Hebrew Drama - Amaar Mohammed Hattab ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2020)
Realism is described as a unique phenomenon and have had properties and features. It works under materialistic, environmental, sociological, and psychological factors as well as practice, and the historical and civilized heritage. This contributes to form the concept based on special visions and it enables it to be as part of the civilized heritage of the Jewish people. Realism seems innate and naïve in the first drama experiments. The realistic, social, and environmental dimensions appear in it. By using analysis, interpretation, and explanation to solve the details of the living which put a burden on the previous drama generations and all its contradictions on an individuals and society which can create an influencing subject to look up in the dramatist’s mind to find a formulation of the shape and treatment to produce it technically where it contributes to stratitude and social movements. This can be done to make change in the society to get rid of the deadlock and stratification which was produced in the early decades of the twentieth century with the first statements of pioneers of the first and second generation and those who follow them from the third and fourth generation. The realism of the Hebrew drama does not come at one pace but it comes in various ratios. It treats the reality on drama stage rather than real treatment. It makes the receiver and audience lives the atmosphere of the stage and its imagination and techniques. This treatment is deep besides reality by without falling in it. Consequently, the treatment is imaginative not a realistic. Obviously we notice that I’m the works of Yousef Bar Yousef since he is one of the second generation dramatists. We can notice these features and characteristics in his plays such as (The Dot) and (The orchard)